Relationship Between Bioimpedance Vector Displacement and Renal Function After a Marathon in Non-elite Runners - Nescolarde, Lexa; Roca, Emma; Bogónez-Franco, Paco; Hernández-Hermoso, José; Bayes-Genis, Antoni; Ara, Jordi (Frontiers in Physiology, 2020)
PURPOSE: This study investigates the relationship between whole-body bioimpedance vector displacement, using bioelectrical impedance vector analysis and renal function, through serum bi-omarkers (creatinine, urea, sodium, C-reactive protein, creatine kinase) and urine biomarkers after a marathon. METHODS: Nineteen non-elite runners were measured 24 h pre-race, immediately post-race and 48 h post-race. The bioimpedance measurements were analysed by BIVA using the Hotelling’s T2 test. Runners were divided according to a cut-off of serum creatinine level immediately post-race in G1 (1.2 mg/dL of serum creatinine level) and G2 (1.2 mg/dL of serum creatinine level). The increase of serum creatinine levels in 83% of G2 runners was related to acute kidney injury (AKI) stage 1. RESULTS: Neither G1 nor G2 showed a creatinine clearance rate (CCr) lower than 60 mL/min. G2 showed a significant increase in CRP values 48 h post-race compared to baseline than G1 (P0.05) over 5 mg/L (6.8 ~ 15.2) in 92% of the runners and CK values over 215 U/L (282 ~ 1882) 48 h post-race in 100% of the runners. By BIVA, the 95% confidence ellipses of G2 showed short-er bioimpedance vectors than G1 with a noticeable minor Xc/H (P  0.01), indicating an expansion on extracellular water and inflammation. The runners with Xc/H 48 h post-race values ≤ 30.5 Ω with a decrease from -3% to -12% respect to Xc/H value 24 h pre-race, indicated AKI stage 1 with 85.7% sensitivity and 91.7% specificity, with a direct correlation between AKI stage 1 with greater CRP values 48 h post-race and bioimpedance vector displacement but not with CK values 48 h post-race. CONCLUSION: Through this data collection it was evidenced that transient reduction in renal function is more related to inflammatory factors than muscle damage. The BIVA method along with serum biomarkers could be used to follow-up the kidney function in runners.